P–750 Clinical efficacy of virtual reality for acute pain and anxiety management during outpatient hysteroscopy and endometrial biopsy in subfertile patients. (6th August 2021) - Schutyser, V; Buyl, R; Vos, M. D; Tournaye, H; Blockeel, C
Abstract: Study question: Does the use of virtual reality (VR) headsets in diagnostic office hysteroscopy (HSC) with endometrial biopsy (EB) reduce anxiety and pain scores in the patient? Summary answer: Virtual reality during office HSC do not seem to improve relaxation, anxiety, or pain scores. Physicians have a good perception of patients' pain. What is known already: Women undergoing outpatient HSC experience high levels of preoperative anxiety, which increase pain and discomfort during the procedure. The experience of pain is a complex phenomenon, which simultaneously occurs on cognitive, emotional, and behavioural levels, and is influenced by many factors. A Cochrane review failed to show a significant difference between different types of pain relief (analgesics, local anaesthetic and verbal support techniques …). VR is a multisensory immersion providing an interactive high level distraction, occupying a large portion of humans' finite attentional resources (vision and audio), and leaving less cognitive capacity available to process pain. Study design, size, duration: The sample size for this prospective randomized controlled trial was calculated at 196 patients (98 per group), considering a power of at least 80% to detect superiority of adding a VR headset versus standard care, standard deviation (SD = 2.0), using a two-sided, t-test, at significance level alpha of 0.05. The preliminary results after 1 month include a sample of 48 patients: 25 in the VR group and 23 controls. Participants/materials, setting, methods: All 48 patients suffer subfertility and underwent HSC with EB at our tertiary-care fertility center. We used Oncomfort®, a commercially available VR autohypnosis relaxation program designed for perioperative settings. The headmounted smartphone display with headphones provides image sound distraction with suggestive hypnosis techniques incorporated. Before and immediately after the exam, both patients and surgeons fill out a questionnaire using the 10.0cm visual analog scale (VAS). Main results and the role of chance: The mean duration of HSC was 3min43sec in the VR group, (range 2–6min), compared to 4min50 in the control group (range 1–12minutes), which was not significantly different (p = 0.09). Subjective variables of stress, anxiety and pain were evaluated at four different time points, i.e. before, during, immediately after HSC and one week later. According to VAS, stress levels did not differ significantly (p > 0.05) between the VR group and the control group, or within time: 5.08 to 5.36 to 3.08 vs 4.48 to 4.83 to 2.48 before, during and after HSC respectively. Fear levels prior to HSC at 4.28 for VR patients and 3.52 for controls did not increase significantly during HSC in both groups: 4.44 vs 4.17. During HSC, pain levels increased from 1.40 to 4.720 in the VR group vs 0.65 to 4.109 (NS) in the controls, to decrease again afterwards to 2.60 vs 2.17 (NS) respectively. Physicians rated the average pain levels of VR patients as 3.32 compared to 3.0 for controls, which was significantly correlated to patients' perception (p < 0, 005). Patients gave a positive rating to the VR experience (satisfaction score 7.17). Limitations, reasons for caution: These are preliminary results, evaluating only a fourth of the required sample. A population selection bias could exist, as recruited patients were willing to accept VR. The very short induction period of 2 minutes could influence the effect of (immersiveness into) VR. Wider implications of the findings: Pain management in ambulatory procedures should be multimodal and should include both pharmacological and non-pharmacological interventions. Introducing VR might increase patient tolerance for longer or more painful procedures. Offering a range of options will increase the spectrum of successful procedures in the outpatient setting and improve patient experience. Trial registration number: B.U.N. 1432020000050